DOI: 10.20868/upm.thesis.9588
|View full text |Cite
|
Sign up to set email alerts
|

Agentes animados personificados en sistemas interactivos: diseño y evaluación

Abstract: xiii la que tanto niños como profesores adquieren un papel activo. De esta experiencia se crean dos aplicaciones: Emo y Animaddin. Con ellas se muestra el éxito de la tecnología de los Agentes Animados Personificados como complemento motivador para incitar e involucrar a los niños en la interacción, como patrón gestual de imitación para expresar emociones, y como refuerzo para afianzar el aprendizaje. Por otra parte se observa la necesidad de revisión continua del comportamiento y la apariencia del Agente Anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…Communication problem management in dialogue systems deals with the prevention, detection and graceful recovery from these delicate situations (López Mencía, 2011).…”
Section: Management Of Communication Problemsmentioning
confidence: 99%
See 4 more Smart Citations
“…Communication problem management in dialogue systems deals with the prevention, detection and graceful recovery from these delicate situations (López Mencía, 2011).…”
Section: Management Of Communication Problemsmentioning
confidence: 99%
“…Mental and behavioural aspects such as personality traits, social role, emotional state and discursive attitude (e.g., passive vs. proactive) are also aspects to take into account when designing (and evaluating) ECAs, for their communicative value and for the effect they may in turn hav on th us rs' b haviour an on th ir subjective experience (López Mencía, 2011). Hone (2006) has observed that static (i.e., non-animated) embodied agents can help limit user frustration in error recovery processes when affective communication strategies are employed.…”
Section: Mental States Appearance Learning and Social Effectsmentioning
confidence: 99%
See 3 more Smart Citations